Patatin-like phospholipase domain containing 3-gene (adiponutrin), preptin, kisspeptin and amylin regulates oocyte developmental capacity in PCOS - Celik, Nilufer; Aydin, Suleyman; Ugur, Kader; Yardim, Meltem; Acet, Mustafa; Yavuzkir, Seyda; Celik, Onder (C M B Assoc, 2018)
This study was planned to test whether follicular fluid (FF) levels of patatin-like phospholipase domain containing 3-gene (PNPLA3:adiponutrin), preptin, kisspeptin, and amylin change in polycystic ovarian syndrome (PCOS). A total of 40 infertile volunteers undergoing IVF/ICSI were included in the study. They were divided into two groups as PCOS (n=20) and control group without PCOS (n=20). The controls were recruited from subjects with a poor ovarian response. The PCOS and control participants were matched according to their body mass index (BMI). Each group of participants underwent ovarian stimulation with GnRH antagonist protocol. Blood and FF samples of one dominant follicle were obtained from each subject during the oocyte pick-up. FF and serum levels of PNPLA3, preptin, kisspeptin and amylin were measured through ELISA. Amylin and adiponutrin median values were not different according to study groups (p>0.05). FF-preptin median values in the control group were similar to the serum preptin values of control and PCOS groups (Z=0.970. p=1.000 and Z=2.631, p=0.051, respectively). Medians of the serum preptin in control and PCOS groups were the same (Z=1.649; p=0.595). FF-preptin median values of PCOS group were significantly lower than the preptin median values of the control group. Serum preptin levels were positively correlated with HOMA-IR, but not with pregnancy rates and the number of retrieved oocytes. Scrum kisspeptin levels were negatively correlated with the number of retrieved oocytes and pregnancy rates. While amylin and adiponutrin have no role in the folliculogenesis, kisspeptin and preptin work together for regulating follicle developmental capacity in PCOS.
Keywords: PCOS; Follicular fluid; IVF/ICSI; PNPLA3; Preptin; Kisspeptin; Amylin